Apple Can Act as Anti-Aging on Yeast Cells. (30th August 2012) - Palermo, Vanessa; Mattivi, Fulvio; Silvestri, Romano; La Regina, Giuseppe; Falcone, Claudio; Mazzoni, Cristina
Abstract : In recent years, epidemiological and biochemical studies have shown that eating apples is associated with reduction of occurrence of cancer, degenerative, and cardiovascular diseases. This association is often attributed to the presence of antioxidants such as ascorbic acid (vitamin C) and polyphenols. The substances that hinder the presence of free radicals are also able to protect cells from aging. In our laboratory we used yeast, a unicellular eukaryotic organism, to determine in vivo efficacy of entire apples and their components, such as flesh, skin and polyphenolic fraction, to influence aging and oxidative stress. Our results indicate that all the apple components increase lifespan, with the best result given by the whole fruit, indicating a cooperative role of all apple components.